2019
DOI: 10.3390/nu11071550
|View full text |Cite
|
Sign up to set email alerts
|

Practical Hydration Solutions for Sports

Abstract: Personalized hydration strategies play a key role in optimizing the performance and safety of athletes during sporting activities. Clinicians should be aware of the many physiological, behavioral, logistical and psychological issues that determine both the athlete’s fluid needs during sport and his/her opportunity to address them; these are often specific to the environment, the event and the individual athlete. In this paper we address the major considerations for assessing hydration status in athletes and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 56 publications
1
78
0
24
Order By: Relevance
“…Individuals with salty sweat (e.g., [Cl − ] and [Na + ] ≥ 70 to 80 mmol/L) have an increased risk of NaCl imbalances during prolonged periods of heavy sweating (Baker 2019;Montain et al 2006). Because of the large inter-individual variability in sweating rate and sweat [Na + ] personalized fluid/Na + replacement strategies are recommended to maintain fluid and Na + balance during exercise (Belval et al 2019;McDermott et al 2017;Sawka et al 2007).…”
Section: Electrolytes (Sodium Chloride and Potassium)mentioning
confidence: 99%
“…Individuals with salty sweat (e.g., [Cl − ] and [Na + ] ≥ 70 to 80 mmol/L) have an increased risk of NaCl imbalances during prolonged periods of heavy sweating (Baker 2019;Montain et al 2006). Because of the large inter-individual variability in sweating rate and sweat [Na + ] personalized fluid/Na + replacement strategies are recommended to maintain fluid and Na + balance during exercise (Belval et al 2019;McDermott et al 2017;Sawka et al 2007).…”
Section: Electrolytes (Sodium Chloride and Potassium)mentioning
confidence: 99%
“…Unter Ruhe-und Alltagsbedingungen ist das Durstgefühl zur Regulation des individuellen Getränkekonsums meist ausreichend. Auch Aktiven wird empfohlen, während der Aktivität erst dann zu trinken, wenn sie Durst empfinden -ein Sportbeginn im gut hydrierten Zustand vorausgesetzt [23]. Im Wettkampf kann das Durstempfinden allerdings wegen der Ausschüttung von Stresshormonen un-terdrückt werden.…”
Section: Link Hydr Atationstestunclassified
“…B. Laufstrecken bis 10 km, sind Wasserverluste von mehr als 2 % des Körpergewichts unwahrscheinlich. Daher müsste derselbe Athlet während des Sports keine Getränke aufnehmen [23].…”
Section: Für Wasserausgleich Sorgenunclassified
“…Due to the nature of the sport, soccer players have limited access to fluids and time to rehydrate as there are no timeouts and minimal player substitutions [ 2 ]. The requirements of high intensity exercise combined with limited fluid availability puts players at a high risk of hypohydration, which can be further exacerbated by warm/hot and humid environmental conditions [ 3 , 4 ]. Fédération Internationale de Football Association (FIFA) declares hydration breaks at the 30th and 75th min of each 90 min match when environmental stress, assessed via wet-bulb globe temperature (WBGT), is greater than 31 °C.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication by Belval et al (2019) suggested that personalized hydration strategies are necessary to promote adequate hydration and optimize performance based on the exercise intensity, fluid availability, and environmental condition of each sport [ 4 ]. In competitive soccer, players exhibit different exercise characteristics (sprinting, running, walking, and standing) depending on on-field positions.…”
Section: Introductionmentioning
confidence: 99%